Omacetaxine mepesuccinate prevents cytokine-dependent resistance to nilotinib in vitro: potential role of the common β-subunit c of cytokine receptors - Klag, Thomas-Matthias; Härtel, Nicolai; Erben, Philipp; Schwaab, Juliana (Leukemia, 2012)
Overcoming resistance against BCR-ABL-inhibitors in chronic myeloid leukemia (CML) is central to prevent progression to advanced phase disease. Kinase mutations of BCR-ABL and cytokine-mediated modulation of response to tyrosine kinase inhibitors (TKIs) are key mechanisms governing clinical response to imatinib and second generation TKIs. Omacetaxine mepesuccinate is effective in imatinib-resistant CML with reported stem cell activity. We specifically thought to explore omacetaxine in the context of the pan-resistant mutant T315I, and in its potential to modify cytokine-dependent resistance. Omacetaxine was investigated in cell lines and primary CD34+ enriched progenitor cells from patients with CML. Addition of cytokines, shown to revert the efficacy of TKIs in BCR-ABL-positive cells, does not affect omacetaxine mediated antiproliferative activity, neither in cell lines nor in primary CML CD34+ progenitor cells. Looking at potential mechanisms, we found marked downregulation of the common β-subunit c of the cytokine-receptors (cCRβc) for IL3, IL5 and GM-CSF by omacetaxine in cell lines and primary progenitor cultures. The observed cytokine-independent in-vitro cytotoxicity of omacetaxine may be explained by downregulation of cCRβc. Whether this can be used clinically as a means to optimize the stem cell activity of TKIs merits further evaluation.
Gesehen am 04.02.2019